GUIDELINES FOR DEVELOPING THE EMOTIONAL INTELLIGENCE OF EDUCATIONAL INSTITUTION ADMINISTRATORS PRIMARY SCHOOL UNDER THE JURISDICTION OF THE PHICHIT PRIMARY EDUCATIONAL SERVICE AREA OFFICE, AREA 2, ACCORDING TO THE PRINCIPLES OF PHAWANA 4 - Kaewliam, Kittiphon; Thammavajirathirakhun; Chaengjit, Suwat (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims to 1) study the emotional intelligence of school administrators and 2) find a way to develop emotional intelligence of school administrators according to the Four meditation principles (Bhvana). This research is a mixed-method research. The quantitative research used a questionnaire with a sample of 302 teachers. Data were analyzed using statistics, including frequency, percentage, mean, and standard deviation. Qualitative research was conducted by interviewing 9 key informants. Data were analyzed using content analysis. The research results found that 1) Overall, the emotional intelligence of school administrators in schools under the Office of the Primary Educational Service Area 2, Phichit, was at a moderate level. When considering each aspect, all 5 aspects were at a moderate level: self-control of emotions, social skills, self-motivation, self-awareness of emotions, and understanding others’ emotions, respectively. 2) The development guidelines for emotional intelligence of school administrators according to the Four meditation principles (Bhvana) consisted of (1) self-awareness of emotions, understanding and listening to others’ feelings, controlling emotions and problem-solving mindfully, and giving feedback and praising teachers for expressing their opinions. (2) Self-control of emotions: Creating an understanding of both positive and negative changes, created an open and supportive atmosphere for teachers to seek knowledge and adapt to the situation. (3) Self-motivation: Developing yourself in both theory and practice, supporting communication skills in working with others, practicing new skills to learn. (4) Understanding others' emotions: Building an understanding of others' perspectives, reducing conflicts and finding solutions together, learning how to manage others' emotions, building good relationships and working smoothly with others. (5) Social skills: Building communication and interaction with others appropriately, providing opportunities to invite open and friendly conversations.